Excesiva onerosidad, hardship y cláusula hardship - García Long, Sergio (2024)
From a comparative and transnational perspective, this work focus on the phenomenon of unexpected circumstances in contracts, and specifically, on hardship and the various models of hardship proposed by (i) civil codifications, (ii) international uniform law instruments, and (iii) international contractual practice. The pandemic made hardship fashionable, but with that was revealed that hardship was not really understood. To fix that, it is needed a study which includes the three levels of analysis aforementioned and to distinguish between excessive onerosity, hardship and hardship clause. Only this will allow to understand the real extension of hardship in contracts and the interaction of its models between Civil Law and Common Law.